Design, technology, nature: a cross-cutting approach - Mario Losasso (Techne, 2025)
The special series issue of Techne journal – an expression of SITdA, the Italian Society of Architectural Technology – shares the contents that emerged in the “Beyond All Limits” Conference (2022) held under the scientific patronage of SITdA. The topics of the papers can be identified in disciplinary fields presenting an interaction between people, technology, society and nature, and also ecosystemic sensitivity. The papers reflect the viewpoints of several institutional and academic representatives, associations engaged in the field of university education, many scholars and researchers of different scientific-disciplinary domains of design culture and innovation. Today the scientific community is aware that such an approach can significantly contribute to the sustainable evolution of the design urbanistic and architectural area in its trans-scalar, multidisciplinary and challenging dimension, overcoming technocratic responses to a demand that requires integration of the humanistic and technical-scientific dimensions.